Revolutionizing regeneration of NADH and deoxygenation of sulfide: Harnessing visible light with SDG@TPP composites for powerful synthetic applications - Kumari L.; Singh S.; Yadav R.K.; Shahin R.; Kim T.W.; Pandey S.K.; Tiwari D.; Singh A.K.; Satyanath; Dwivedi D.K.; Gupta N.K. (My University, 2025)
Aqueous ascorbic acid splitting through photocatalysis is a potential method for turning solar energy into value-added compounds. As a result, converting solar light into green solar fine chemicals in an ecologically responsible and cost-effective manner remains a difficult issue. The solvothermal approach was used to effectively construct an SDG@TPP composite photocatalyst.To that end, we present here the synthesis and development of a sulfur-doped graphene (SDG)-based visible light active composite photocatalyst (SDG@TPP), in which SDG interacts with TPP (tetraphenyl porphyrin) through - stacking. Due to its high molar extinction coefficient and delayed recombination features, the newly manufactured SDG@TPP photocatalyst acts in a highly effective way, resulting in higher NADH regeneration (66.1 %) and sulfoxide deoxygenation than SDG photocatalyst. More importantly, a little quantity of TPP on the surface of SDG can efficiently stimulate photoelectron injection and improved photocatalytic activity. This research should shed light on how to create metal-free SDG@TPP composites with good solar energy conversion. © 2023